The Influence of Technology Adaptation, Numeracy Literacy, and Student Conditions on Independent Curriculum Learning - Asmawan, Moh. Chairil; Khotimah, Siti Khusnul; Jatmika, Surya (Proceedings International Conference on Education Innovation and Social Science, 2024)
The transformation of education in the era of society 5.0 is the existence of an independent learning curriculum. This transformation can also be seen in the presence of various policies in the independent learning curriculum. The implementation of independent curriculum learning can run well and smoothly influenced by various factors. The aim of the study was to examine whether there was any effect of technological adaptation, numeracy literacy, and students' conditions on independent curriculum learning. Quantitative research with a correlational research design, while the instrument in this study was a questionnaire using the Google form platform. The population in this study were students at SMK Muhamamdiyah 3 Gemolong who had implemented independent curriculum learning with a sample of 56 respondents. The data analysis technique used is multiple regression analysis technique. From the analysis of existing data, the following research results are obtained: 1) technological adaptation has a significant effect on independent curriculum learning as indicated by the t value of 3.182; 2) numeracy literacy does not have a significant effect on independent curriculum learning as indicated by the t-value of -0.936; 3) the condition of the students has a significant effect on the independent curriculum learning indicated by the t value of 2.38; 4) technological adaptation, numeracy literacy, and students' conditions have a significant effect on learning the independent curriculum together with a percentage of 36.7%.